Composite material of tribotechnical purpose - Уманский, А.П.; Пугачевская, Е.П.; Марценюк, И.С. (Problems of Tribology, 2014)
The new composite material on the base of titanium-chrome diboride with nikel-chromium binder has been developed. The physical-mechanical, physical-chemical and tribotechnical properties of material have been researched. It has been conducted comparative analysis of physical-mechanical properties of developed material and hard alloy WC6. Tests of composite materials TBHN and titanium alloys in fretting-corrosion conditions in different combinations of friction pairs have been conducted. The wear mechanisms of titanium alloys and composite materials on the base of titanium-chromium diboride in fretting-corrosion conditions have been investigated.